2006
DOI: 10.1182/blood-2006-07-034124
|View full text |Cite
|
Sign up to set email alerts
|

Identification of BMP9 and BMP10 as functional activators of the orphan activin receptor-like kinase 1 (ALK1) in endothelial cells

Abstract: ALK1 is an endothelial-specific type I receptor of the TGF␤ receptor family whose heterozygous mutations cause hereditary hemorrhagic telangiectasia type 2. Although TGF␤1 and TGF␤3 have been shown to bind ALK1 under specific experimental conditions, they may not represent the physiological ligands for this receptor. In the present study, we demonstrate that BMP9 induces the phosphorylation of Smad1/5/8 in microvascular endothelial cells, and this phosphorylation lasts over a period of 24 hours. BMP9 also acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
676
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 622 publications
(716 citation statements)
references
References 44 publications
33
676
3
4
Order By: Relevance
“…Figure 5 A shows staining for AlkP activity in mrSCs treated with BMP-9 in the presence of 5Â and 20Â molar equivalents of soluble ALK1-Fc receptor, which can bind and specifically inhibit BMP-9. (15) Our results indicated that the level of osteogenesis of mrSCs induced by BMP-9 was inversely proportional to the level of soluble ALK1-Fc receptor added.…”
Section: Bmp-9-induced Ho Is Prevented By the Soluble Alk1 Receptormentioning
confidence: 55%
See 1 more Smart Citation
“…Figure 5 A shows staining for AlkP activity in mrSCs treated with BMP-9 in the presence of 5Â and 20Â molar equivalents of soluble ALK1-Fc receptor, which can bind and specifically inhibit BMP-9. (15) Our results indicated that the level of osteogenesis of mrSCs induced by BMP-9 was inversely proportional to the level of soluble ALK1-Fc receptor added.…”
Section: Bmp-9-induced Ho Is Prevented By the Soluble Alk1 Receptormentioning
confidence: 55%
“…(14) BMP-9 is the physiologic ligand of the endothelial type I ALK1 receptor in association with the type II BMP receptor (BMPRII). (15) ALK1 is one of the seven type I receptors for TGF-b family members. (16) The activation of ALK1 induces the phosphorylation of receptor-regulated Smad-1 and Smad-5 and their accumulation in the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…While BMP-9-induced heterotopic ossification was shown to be mediated through the ALK1 type 1 receptor, the study does not address whether ALK1 acts independently of other BMP type 1 receptors or other receptors contribute to heterotopic ossification, perhaps through type 1 BMP receptor heterodimer formation with ALK1. Although experimental data support that ALK1 binds BMP-9 and activates the BMP-Smad1/5/ 8 pathway in response to BMP-9, (11) there is additional evidence that BMP-9 binds to and signals through receptors other than ALK1, including ALK2, (12,13) the BMP type 1 receptor that is mutated in patients with FOP. (4) It is interesting to speculate that in these experiments, BMP-9 in the context of injury is inducing heterotopic ossification by activating ALK1-ALK2 heterodimers or that a sequential series of BMP signaling events mediated independently by ALK1 and ALK2 is required for induction of heterotopic ossification.…”
mentioning
confidence: 99%
“…Interestingly, ALK1 was identified initially as an endothelial-specific type 1 receptor. (11) It also cannot be overlooked that heterotopic bone is a tissue that frequently forms through endochondral ossification and is comprised of multiple cell types. While the brunt of investigations of heterotopic bone formation has focused on osteoblast formation and differentiation, recruitment and differentiation of additional cell types are critical to the process as well.…”
mentioning
confidence: 99%
“…Two recent reports show that ALK-1 may instead signal through BMP-9 and that endoglin can potentiate the signal, suggesting that BMP-9 may represent a physiologically relevant endothelial signaling pathway for HHT pathogenesis [17,52]. Endothelial cell-specific ablation of the murine Alk-1 gene causes AVM formation during development, whereas mice harboring an EC-specific knockout of Alk-5 (the type I TGF-β receptor) or TbRII (the type II TGF-β receptor) show neither AVM formation nor any other perturbation in vascular morphogenesis [42].…”
Section: Mendelian Diseasementioning
confidence: 99%